Praktek Etika Bisnis Dalam Perspektif Ekonomi Syari’ah: Bisnis Syariah - Gunawan, Aan; Uyun, Muhamad; Rohmatika, Idha Ismalia (Institute of Research and Community Service at Islamic University of Bunga Bangsa Cirebon, 2023)
Abstract The market is a meeting place for traders and buyers. The products or goods that are often traded in the market consist of fruits, rice, meat, fish, vegetables, spices, clothing and electronic equipment. To gain profit and sympathy from consumers, traders or business people often use strategies including product strategy, pricing strategy, and promotion strategy. However, most of the strategies they apply are not in accordance with the principles of shari'ah business ethics, including frequently reducing the amount of measure, hiding defective goods, playing with prices and frequently committing perjury.This research is included in field research, namely a study whose purpose is to look closely and intensively at a social event, namely the practice of business ethics from the perspective of Islamic economics. The essence of this research is descriptive-analytic research, namely research that aims to find, describe problems. To obtain the information needed in research, researchers used observation, interviews and documentation. After analyzing the data, the researcher uses qualitative methods and draws conclusions using a deductive approach.Based on the research results, it can be concluded that traders or businessmen, especially in traditional markets, often carry out strategies that are not in accordance with Shari'ah business ethics. Therefore, so that the actions of traders can be in accordance with Sharia business ethics, traders must apply the principles of shari'ah business ethics, namely honesty, trustworthiness and openness or transparency.